Self-deception and shifting degrees of belief. (17th November 2019) - Chan, Chi Yin; Rowbottom, Darrell P.
ABSTRACT: A major problem posed by cases of self-deception concerns the inconsistent behavior of the self-deceived subject (SDS). How can this be accounted for, in terms of propositional attitudes and other mental states? In this paper, we argue that key problems with two recent putative solutions, due to Mele and Archer, are avoided by "the shifting view" that has been advanced elsewhere in order to explain cases where professed beliefs conflict with actions. We show that self-deceived agents may possess highly unstable degrees of belief concerning the matters about which they are self-deceived.